Experimental study on tracer gas method for building infiltration rate measurement. (November 2020) - Men, Chuanling; Wang, Shangwen; Zou, Zhijun
The use of occupant-exhaled CO2 as the tracer gas enables the actual indoor infiltration rate to be measured, but the number and location of measuring points have a great impact on the accuracy of the results. This paper compares the experimental results from two tracer gas measurement techniques, decay with SF6 and constant injection with CO2 (exhaled by occupant). The results show a deviation of –9.0 to 7.4% between these two methods. This paper compares the result of this study with previous ones, and it confirmed that the CO2 method is an effective technique to calculate the infiltration rate in a room with a certain air volume when one measuring point is provided, and this is more accurate with good mixing of the indoor air. The impact of the measurement duration and distribution of indoor air on the measurement accuracy are also analysed. It is found that an extended monitoring period can reduce the impact of indoor air distribution. In actual measurements in residential building, it is recommended to select the data after occupants have been in the room for half an hour and to take measurements over 1 h after that. Practical application : Accurate air change per hour (ACH) is beneficial to the study of building energy consumption and indoor air quality. This paper explores the effectiveness of CO2 method, which provides useful reference for the large sample measurements of infiltration rates in residential buildings.